Notes for the information of members of the committee on the present conditions as to midwifery
1928 1928 1920s 4 pages -2- The numbers practising in 1926 according to the returns of the Local Supervising Authorities was 14,411. Of these 12,785 or 88.7% are trained. 1,628 or 11.3% are untrained. During the year 16,436 midwives signified their intention of practising. This is an increase of 154 on the previous year. Of the rural population, 78% of the population are provided with services of trained midwives as compared with 71% five years ago. TRAINING. Under the Midwives' Act 1902 the period of training for midwives was three months. In June 1916, this was extended to six month [months] for untrained women and four months for certain trained nurses. Since May 1926 the pupil midwife who is not a nurse has to undergo a training of one year before she can sit for the C.M.B. Certificate, and the trained nurse six months. The Report of the C.M.B. for 1926-7 states that there are 192 Institutions and Homes for training in England and Wales. 66 of these are Poor Law Institutions. 64 practising midwives are approved as teachers. 107 registered medical practitioners hold special approval of the Board as lecturers. The co-operation of the Universities is being more and more sought to facilitate the centralization of lectures and the formation of adequately large lecture classes. Universities are lending assistance and arrangements have already been made with Durham, at Newcastle-on-Tyne, Leeds and Birmingham. TRAINING OF MIDWIVES IN OTHER COUNTRIES. In Sweden the period of training is two years. It is conducted in the big maternity hospitals. The midwives are usually well educated as the service attracts good people. It is stated that no woman in Sweden is attended by a medical practitioner at her confinement unless there are complications. Of all the confinements in Sweden 30% take place in maternity hospitals. In Holland the training covers three years. The first year is spent largely in general education and in the theory of midwifery practice. During the second year instruction in theory is continued and some practical work is undertaken. An examination is held at the end of the second year. During the third year pupils work on the district and the welfare centres etc. in addition to continuing lectures and practice in hospital, and a practical examination is held towards the end of the period. All pupils must deliver 10 cases in hospital and 10 outside, but they usually get 50 or 60 deliveries. In France the course of training for midwives is two years and both midwifery students and pupil midwives are trained in the necessary technique by the heads of wards in the Maternity Hospitals. 292/824/1/117